PENGARUH IKLIM ORGANISASI DAN MOTIVASI KERJA PADA KEPUASAN KERJA PEGAWAI BALAI WILAYAH SUNGAI BALI - PENIDA - Rahmawati, Sarah; Supartha, Wayan Gede (E-Jurnal Manajemen, 2015)
Job satisfaction is a pleasant emotional state employees are reflected by the positive attitude of employees towards work. So that employees have a high level of job satisfaction, an organization needs to consider factors that affect job satisfaction. The purpose of this study was to analyze the influence of organizational climate and work motivation on employee job satisfaction. This research was conducted at the Center for River Basin Bali -Penida. The number of samples taken are 139 people with a simple random sampling method. Data collected through interviews, observations and questionnaires. Data analysis technique used is multiple linear regression. Based on the analysis found that partial organizational climate and work motivation positive and significant impact on job satisfaction of employees in the Central River Region Bali - Penida. These results indicate that the better the organizational climate of job satisfaction will increase, so does the motivation to work, the higher the work motivation job satisfaction increases.
Keywords: Organizational Climate, Work Motivation, Job Satisfaction